Strategi Peningkatan Moral Siswa di Era Digital: Kajian Sosiologis tentang Integrasi Edukasi Karakter dan Media Pembelajaran Interaktif di SMA Negeri 12 Pontianak - Octy Astrid Nasution; Yohanes Bahari (Journal on Education, 2024)
Enhancing student morale in the digital era has become an increasingly important concern in education. In this context, this study focuses on how the integration of character education and interactive learning media can improve student morale in the digital era. This research aims to find out how the integration of character education and interactive learning media can improve student morale in the digital era and test whether the "Social Learning Theory" or the "Self-Determination Theory" theory is more relevant. to the phenomenon of increasing student enthusiasm in the digital era. The research approach is a qualitative approach using structured and unstructured interview methods. The method of this study was conducted by conducting structured and unstructured interviews with 20 students of SMA Negeri 12 Pontianak who were randomly selected. The collected data was then analyzed using thematic analysis and content analysis. The instruments of this study are structured and unstructured interviews that are used to collect data on how students at SMA Negeri 12 Pontianak understand and apply moral values ​​in their daily lives. The total number of participants in this study was 20 students of SMA Negeri 12 Pontianak who were randomly selected. The data analysis techniques used in this study are theme analysis and content analysis. The results of the study show that the integration of character education and interactive learning media can improve student morale in the digital era. Interview data shows that students who follow the character education integration program and interactive learning media have a higher level of morale than students who do not follow the program. The conclusion from this study is that the integration of character education and interactive learning media can improve student morale in the digital era. The suggestion is that teachers need to use interactive learning media that are more effective in improving student morale and integrating character education in the learning process.